2006
DOI: 10.1152/ajpcell.00015.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transport mechanisms and determinants critical for Na+-dependent Pi symport of the PiT family paralogs human PiT1 and PiT2

Abstract: . Characterization of transport mechanisms and determinants critical for Na ϩ -dependent Pi symport of the PiT family paralogs human PiT1 and PiT2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
44
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 46 publications
9
44
1
Order By: Relevance
“…In the absence of Na + , lowering pH from 7.5 to 6.0 induced significant P i uptake in Xenopus oocytes that expressed PiT-2. This finding suggests that H + may also substitute for Na + for this isoform (Bottger, Hede et al 2006;). The increased K 0.5…”
Section: Slc20mentioning
confidence: 92%
See 1 more Smart Citation
“…In the absence of Na + , lowering pH from 7.5 to 6.0 induced significant P i uptake in Xenopus oocytes that expressed PiT-2. This finding suggests that H + may also substitute for Na + for this isoform (Bottger, Hede et al 2006;). The increased K 0.5…”
Section: Slc20mentioning
confidence: 92%
“…(Kavanaugh, Miller et al 1994;Bai, Collins et al 2000;Bottger, Hede et al 2006;Ravera, Virkki et al 2007)). A cooperative P i -dependence was reported for PiT-2 expressed in Xenopus oocytes under non-voltage clamped conditions, a finding consistent with this isoform behaving as a functional dimer (Bottger, Hede et al 2006). This finding has yet to be confirmed under voltage-clamp conditions.…”
Section: Slc20mentioning
confidence: 99%
“…We have found that VSMCs exhibit both Na-dependent and Naindependent Pi transport components with similar kinetic behavior, but that only the Na-coupled saturable uptake can be explained by the expression of both type III NaPi (NaPi-III) transporters, Pit1 and Pit2. 14 As an article has recently been published regarding the characteristics of Pi transport by Pit1 and Pit2 while preparing this manuscript, 15 this article will focus on the different and novel findings we have found.…”
mentioning
confidence: 98%
“…From these and other studies (e.g. (Bai et al, 2000;Bottger et al, 2006;Olah et al, 1994)) it became apparent that SLC20 proteins were functionally distinct from SLC34 proteins. These differences were highlighted in a detailed characterization of PiT-1 transport kinetics .…”
Section: Kineticsmentioning
confidence: 76%
“…Unlike SLC34 proteins that are exclusively Na + drive, for PiT-1, Li + can fully replace Na + as the driving cation, albeit with a significantly reduced transport rate . Furthermore, in the absence of Na + , lowering pH from 7.5 to 6.0 induces significant P i uptake in Xenopus oocytes that expressed PiT-2, which suggest that H + may also substitute for Na + for this isoform (Bottger et al, 2006;Villa-Bellosta et al, 2007). Na + is the first ion to interact followed by a random binding of Na + and P i .…”
Section: Kineticsmentioning
confidence: 99%